Staff perspectives from Australian hospitals seeking to improve implementation of thrombolysis care for acute stroke. (July 2019) - Paul, Christine; D'Este, Catherine; Ryan, Annika; Jayakody, Amanda; Attia, John; Oldmeadow, Christopher; Kerr, Erin; Henskens, Frans; Grady, Alice; Levi, Christopher R
Background: Intravenous thrombolysis is one of few evidence-based treatments for acute stroke. Treatment uptake is low outside major stroke care centres. There is a need for greater understanding of barriers encountered by clinicians when seeking to increase thrombolysis rates. Aim: The aim of this study is to describe physicians' and nurses' perceptions regarding thrombolysis for acute stroke at hospitals in the earlier stages of thrombolysis implementation. Methods: A cross-sectional paper survey completed by physicians' and nurses' was distributed to 1127 staff at stroke care units, emergency departments or equivalent stroke care facilities at 19 Australian hospitals, as part of a cluster randomised controlled trial for thrombolysis implementation and systems improvement. Results: Of 1127 potential participants, 503 (148 physicians and 355 nurses) completed surveys (45% response rate). Over 90% agreed that thrombolysis improved the odds of independent survival. However, 42% to 58% agreed that there were limitations in the evidence base. A small proportion of staff indicated deficits in technical competencies. Interactive or competency-based training was reported by less than two-thirds of the sample. Challenges such as quick bed availability were identified. Emergency department physicians were less positive towards the treatment compared with nurses (p < 0.001), stroke care unit physicians were more positive than nurses (p = 0.047) and older clinicians were more positive than younger clinicians (p = 0.007). Conclusion: Australian hospitals seeking to address barriers to stroke thrombolysis implementation may benefit from the availability of interactive and competency-based training, staff performance feedback, support to make beds available quickly and bypass arrangements to quickly deliver acute stroke patients to appropriate facilities.